A pedagogy of emotion in teaching about social movement learning. Issue 2 (17th February 2016) - Walker, Judith; Palacios, Carolina
ABSTRACT: This article explores the role of emotion in teaching about social issues in higher education. We draw and expand upon Boler's notion of a 'Pedagogy of Discomfort', Goodman's and Curry-Steven's concept of a 'Pedagogy for the Privileged', and on Freire's idea of a 'Pedagogy of Hope', in reflecting on our own experiences in teaching a graduate-level course on social movement learning. We argue for the importance of further sociological theorisation of the role of emotion in teaching and learning in higher education, and acknowledge the challenges a Pedagogy of Emotion present to those teaching in the social sciences at the post-secondary level.